IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM MENERTIBKAN PEDAGANG KAKI LIMA DI PASAR SENTRAL KABUPATEN BANTAENG (Fakultas Dakwah dan Komunikasi, 2020)
The journal that was made aims to describe the implementation of local government policies in curbing street vendors. The explanation of this article is obtained from the results of literature studies from various readings such as journals, books and direct interviews with policemen and street vendors. The increasing disorder in the market shows the importance of local government policies in curbing street vendors. The results of the analysis show that local government policies determine the success or failure of an enforcement process. With the existence of a policy from the local government, it can be implemented in controlling street vendors.